User experiences of an American-adapted moderated online social media platform for first-episode psychosis: Qualitative analysis - Elena L Pokowitz; Bryan J Stiles; Riya Thomas; Katherine Bullard; Kelsey A Ludwig; John F Gleeson; Mario Alvarez-Jimenez; Diana O Perkins; David L Penn (Digital Health, 2023)
Objectives The current study sought to qualitatively characterize the experiences of American users in a recent open trial of the Horyzons digital platform. Methods In total, 20 users on Horyzons USA completed semistructured interviews 12 weeks after their orientation to the platform and addressed questions related to (1) the platform, (2) their online therapist, and (3) the peer workers and community space. A hybrid inductive-deductive coding strategy was used to conduct a thematic analysis of the data (NCT04673851). Results The authors identified seven prominent themes that mapped onto the three components of self-determination theory. Features of the platform itself as well as inter- and intra-personal factors supported the autonomous use of Horyzons. Users also reflected that their perceived competence in social settings and in managing mental health was increased by the familiarity, privacy, and perceived safety of the platform and an emphasis on personalized therapeutic content. The behaviors or traits of online therapists as perceived by users and regular contact with peers and peer support specialists satisfied users’ need for relatedness and promoted confidence in social settings. Users also described aspects of Horyzons USA that challenged their satisfaction of autonomy, competence, and relatedness, highlighting potential areas for future iterations of the platform's content and interface. Conclusions Horyzons USA is a promising digital tool that provides young adults with psychosis with the means to access tailored therapy material on demand and a supportive digital community to aid in the recovery process.